Operations and Patronage of Private Waste Contractors Initiative of Solid Waste Collection in Ibadan Metropolis, Nigeria - Oladeji, Peter B; Oyedare, Adekunle Benjamin; Ogunwale, Taiwo Olusegun; Oyetola, Simeon Oyesoji; Basiru, Taofeek Adekola; Ogunrinola, Oluwaseun Femi (Industrial and Domestic Waste Management, 2024)
The Oyo State Solid Waste Management Authority (OYSWMA) hired private waste operators (PWOs) because the government was unable to handle the increasing amounts of solid garbage that were being carelessly deposited in every corner of the metropolis. This study looked at the private garbage contractors' methods of operation, clientele, and difficulties in managing residential solid waste in Ibadan, Nigeria. In the three local government districts of the metropolis, a structured questionnaire was given to 21 private refuse operators and 250 homes. A few measures of service quality were employed to determine the method of operation and customer base. To interpret the gathered data, both descriptive and inferential statistics were employed. The findings showed that the factors that affected residents and operators of SWM the most were educational attainment, monthly income, building types, and occupation (n = 213, 85.2%; 164, 65.6%). Of the houses who enrolled for waste collection, between 201-300 (47.6%) and 100-200 (42.9%) utilized private waste contractors. Although the license specifies once per week, waste collection is inconsistent and typically occurs once every two weeks (52.4%); charges, on the other hand, are variable and exceed the established rates. Undue financial backing from the LGAs, impassable areas, incompatible law, poor advertisement and awareness, political influence, exorbitant leachate treatment fees, and poor health were among the operational issues confronted the private garbage operators. The elements that affect the way the private sector of SWM operates and attracts customers were found to be as follows: non-cooperation of residents (n = 8, 38.1%), poor nearness to buildings (n = 9, 42.9%), and the lax enforcement of hygiene regulations (n = 4, 19.0%). The report suggests that in order to provide residents in Ibadan Metropolis with high-quality services, private refuse operators should regularly monitor and oversee the collection of solid waste.